Pengaruh Edukasi Kesehatan Pemantauan Tumbuh Kembang Balita dengan Media Leaflet terhadap Kunjungan Posyandu - Cahyaning Setyo Hutomo; Rizka Adela Fatsena (Jurnal Sehat Mandiri, 2024)
Toddler growth and development occur simultaneously, making regular monitoring crucial to detect delays (growth faltering) and enable early interventions. The decline in health visits has hindered the optimal monitoring of toddler growth and development. This study aims to analyze the effect of health education using a leaflet on monitoring toddler growth and development on Posyandu visits. A quasi-experimental design with a pre-post control group approach was applied. Thirty-six toddlers in the Sangkrah Health Center (September–November 2024) were selected via purposive sampling. The inclusion criteria were toddlers in the Sangkrah Health Center area whose parents agreed to participate as respondents, while the exclusion criteria were toddlers with developmental delays. The sample was divided into a control group (18) and an intervention group (18). Data collection included pre-tests (before intervention) and post-tests (for two months after the intervention). The Mann-Whitney U test revealed significant improvements in Posyandu visits in the intervention group (p=0.036), but no changes in the control group (p=0.783). The conclusion of this study is that health education on toddler growth and development using leaflets has an effect on Posyandu visits. This study hopes to establish leaflet-based health education as a foundation for similar programs, especially for mothers with young children.